The incidence of biliary sludge in first trimester pregnancies with hyperemesis gravidarum and its effect on the course of hyperemesis gravidarum. (18th August 2022) - Saglam, Aylin; Derwig, Iris; Sezik, Mekin; Tuncer, Sibel Cigdem; Ozcil, Mustafa D.; Kasap, Burcu; Misirlioglu, Mesut; Alkan, Ender; Ozkan, Namık
Abstract: Pregnancy is one of the risk factors for biliary sludge (BS) formation. In this cross-sectional study, a total of 959 pregnant women were included. Serum aspartate aminotransferase, alanine aminotransferase, sodium, potassium, triglycerides, cholesterol levels and the presence of ketones in urine were determined. The presence of BS was investigated using maternal abdominal ultrasound. The incidence of BS in pregnancies complicated by hyperemesis gravidarum (HG) was 14%. The degree of ketonuria and low birth weight were statistically higher in pregnancies with maternal BS than women without sludge. Total weight gain during pregnancies with BS was statistically lower than controls. The incidence of BS in pregnancies with HG does not appear to increase due to HG-related complications, such as dehydration, starvation and weight loss. However, the severity of HG may be worse when HG is associated with sludge. Impact Statement: What is already known on this subject? The incidence of biliary sludge (BS) in pregnant women ranges between 10.9% and 36%. Some clinical conditions, such as pregnancy, prolonged fasting, total parenteral nutrition, rapid weight loss and ceftriaxone treatment can play a role in the formation of gallbladder sludge. What do the results of this study add? This is the first study to investigate the incidence of BS in hyperemesis gravidarum (HG) pregnancies. Results show that HG may transiently be associated with BS. HG is more likely to cause a transient increase in new sludge formation. The symptoms and complications related to HG may be more severe when HG is associated with BS. What are the implications of these findings for clinical practice and/or further research? Our study showed that BS can be found in HG patients, and HG can be a predisposing factor for new sludge formation, although this association is generally driven by advanced maternal age and increased baseline serum lipid and alanine aminotransferase levels. BS may also be independently associated with an increased risk of subsequent preterm delivery in women with HG.